Pulse oximetry monitoring during non-sedated upper gastrointestinal endoscopy. Issue 837 (July 1995) - Melleney, E. M.; Lambertini, L.; Willoughby, C. P.
Abstract : Fifty consecutive patients judged fit for non-sedated upper gastrointestinal endoscopy were monitored by pulse oximetry before, during and after the procedure. Transient hypoxia developed during intubation in five subjects (10%) but treatment was not required nor was the test halted. Only one patient with pre-existing respiratory problems became hypoxaemic to the extent that oxygen had to be given and the procedure halted. The chance of hypoxia was unrelated to age, sex, smoking, anxiety, or the duration of intubation. Routine pulse oximetry is not necessary for non-sedated gastroscopy but oximetry monitoring may be important in selected cases.